PENGARUH LUMBUNG PANGAN (FOOD ESTATE) GUNA MENINGKATKAN KETAHANAN PANGAN NASIONAL TERHADAP MASYARAKAT (Pusat Unggulan Iptek Ketahanan Pangan Universitas Sultan Ageng Tirtayasa, 2022)
The government continues to strive to fulfill the food needs of the community, one of which is the creation of a food estate program. The food estate program is a long-term government program oriented to the development of food on a large scale with the concept of agriculture based on Science and Technology. The purpose of this food estate program is to serve as a community food reserve so that food availability can always be met from time to time, even if there is a food shortage or food crisis. The purpose of this study was to determine the effect of food estate in increasing national food security for the community. This study uses a qualitative method that briefly discusses the effect of food estate on the community. The results of the study explain that the food estate program, especially because large-scale land clearing has a good impact on improving food security in Indonesia and the role of food estates as food reserves is very beneficial for the community, especially when there is a crisis or food shortage. The food estate program can have a good impact and benefit if the government and the community can work together and be participatory so that this program can succeed.